Strategic Development Formulation for Improving Corporate Mobile Application Engagement Rates (The Asian Journal of Technology Management (AJTM), 2022)
Abstract. In the digital transformation era, one company shifts from manual to digital reporting through a corporate mobile application called JSMART (Jababeka System Management for Advance Report) to serve those living in Kota Jababeka city. JSMART is a corporate application that can be utilized by the community who resides in Jababeka. JSMART was launched in 2017, though unfortunately, based on survey, only 17% of employees are actively using it. The aims of this research are to investigate the root cause of this employee reluctance to adopt the technology and the proposed corporate strategy. The Technology Acceptance Model (TAM) is used in quantitative approach to determine the influence of perceived usefulness, perceived ease of use, and attitudes towards using JSMART amongst employees. Based on path analysis results, these three factors significantly influence one another, and the total mean is calculated as 2.70, which suggests that JSMART is not considered good enough from the perspective of the employees. In addition, interviews were conducted as part of a qualitative approach to investigate further. The root cause mainly arises from organizational factors such as a lack of socialization and training, and unclear rules for utilizing JSMART. Therefore, this study proposes a strategic development formulation that prioritizes organizational development while rejecting a proposed in-app suggestion feature for future development. Keywords:  Corporate mobile application, digital transformation, technology acceptance, engagement rate, strategy.